PENGARUH KONSENTRASI KATALIS ASAM SULFAT DAN WAKTU REAKSI PADA PEMBUATAN BIODIESEL DARI ASAM LEMAK KELAPA SAWIT - Rondang Tambun; Anggara Dwita Burmana; Vikram Alexander (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
This study aims to determine the amount of catalyst and the best reaction time in making biodiesel (methyl ester) from palm fatty acids. The esterification reaction is carried out at 65 oC by using sulphuric acid (H2SO4) as a catalyst. The catalysts used varies from 5 %, 10 %, 15 %, and 20 % to the amount of fatty acid, while the acid value is measured at the reaction time of 60 minutes, 75 minutes, 90 minutes, 105 minutes, and 120 minutes. The molar ratio of methanol and fatty acid varies from 5:1, 6:1, and 7:1. The results obtained show that the acid value increases rapidly from the reaction time of 60 minutes to the reaction time of 105 minutes, and does not increase significantly from the reaction time of 105 minutes to the reaction time of 120 minutes. Based on the acid value obtained, the highest conversion of fatty acids to biodiesel is 97.1250%. This result is obtained at a reaction time of 120 minutes, the amount of catalyst 20 % of the amount of fatty acid, and the molar ratio of methanol and fatty acids 7:1, but this result is almost the same as the conversion of fatty acids at the reaction time of 105 minutes with the same amount of catalyst and molar ratio, that is 96.9286%.